PERBANDINGAN AKURASI TAKSIRAN BERAT JANIN MENGGUNAKAN RUMUS DARE DAN RISANTO DALAM MENENTUKAN PERKIRAAN BERAT BAYI LAHIR DI PRAKTIK BIDAN MANDIRI X TAHUN 2024 - Dino Gagah Prihadianto; Kasih Purwati; Alfath Attarsyah Al’ayubi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Both of high birth weight (HBW) and low birth weight (LBW) infants have the potential to develop health problems during infancy. Most of these problems are related to birth weight, which is a crucial parameter in determining the survival of newborns. Inaccurate fetal weight estimation can lead to undetected problems during pregnancy, thus necessitating research to identify the most accurate fetal weight estimation formula. Methods: This study used a comparative design with a cross-sectional approach. The population in this study was mothers who gave birth at Midwife Practice X in 2024. The sample was determined using non-probability sampling, specifically total sampling. The results were tested using a paired t-test and receiver operating characteristic (ROC). Results: The research results indicated no significant difference between the Dare formula (p-value 0.147) and actual birth weight; however, a significant difference was found between the Risanto formula (p-value 0.000) and actual birth weight. Based on ROC testing, the Dare formula showed an accuracy of 87%, while the Risanto formula had an accuracy of 65%. Conclusion: Fetal weight estimation using the Dare formula demonstrated a higher level of accuracy compared to the Risanto formula in predicting birth weight Keywords: Estimated fetal weight, Birth weight, Maternity